Pengembangan Alat Speed Touch Reaction untuk Latihan Kecepatan Reaksi Pukulan pada Atlet Karate Inkanas Kabupaten Kediri: Penelitian - Choirul Wahyudi; Budiman Agung Pratama; Rendhitya Prima Putra (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Based on purpose Research for develop (development device speed touch reaction For Exercise speed reaction Punch in athletes karate Inkanas Kabupaten Kediri)This study uses development or research and development (RND). Subject research involve 53 athletes karate on 3 twig and branch Dojo black panther yonif 521 Kediri regency. Instrumen using observasi, interview and questionnaire (kuersioner), can be obtained from the research results on 3 twig and branch Dojo black panther yonif 521 show : (1) guidebook( Speed Touch Reaction) which is sized A5, aload description use of tools, rules in the tool Speed Touch Reaction, until ordinances implementation.(2) (Speed Touch Reaction)Have it tested validation, from validation small scale test assessments were Made by expert Media 93,18% expert Materi with presentation 90,90%, expert Praktisi 88,63%, 2 validation by coach karate on 3 twig that is 93,18%, and 23 validation by athletes karate 90,8%, overall go inside category '' very valid''. Validation large scale test assessments were Made by expert Media 95,45%, expert Materi with presentation 97,72%, expert Praktisi 95,45%, 1 validation by coach karate on branch 93,3%, and 30 validation by athletes karate branch Inkanas 93,3%, overall go inside category